Ceramides in Parkinson’s Disease: From Recent Evidence to New Hypotheses - Plotegher, Nicoletta; Bubacco, Luigi; Greggio, Elisa; Civiero, Laura (Frontiers in Neuroscience, 2019)
Ceramides constitute a class of lipids present in the cell membranes where they act as structural components, but they can also work as signaling molecules. Increasing genetic and biochemical evidence supports a link between deregulation of ceramide metabolism in the brain and neurodegeneration. Here, we provide an overview of the genes and cellular pathways that link ceramides with Parkinson’s disease and discuss how ceramide pathobiology is gaining increasing interest in the understanding of the pathological mechanisms that contribute to the disease and in the clinical and therapeutic side.